DETERMINATION OF THE COMPOSITION AND MOLAR VOLUME OF H2O-CO2 FLUID INCLUSIONS BY MICROTHERMOMETRY - Bakker R.J.; Diamond L.W. (My University, 2000)
H2O-CO2 fluid inclusions are common in nature but their accurate analysis by microthermometry has been hindered by insufficient characterisation of the fluid properties along the solvus (high temperature miscibility boundary) of the system. Thus some of the previous methods of calculating fluid inclusion composition (x) and molar volume (V) have relied on notoriously unreliable optical estimates of phase volume fractions. Although the T-V-x properties of the solvus can be modelled thermodynamically from equations of state, a review shows that none of the published equations are accurate enough to be useful in fluid inclusion microthermometry. Therefore, the available experimental data have been used to construct a new V-x diagram, contoured for phase transition temperatures and phase volume fractions. This diagram allows the bulk composition and molar volume of individual fluid inclusions to be determined accurately from two microthermometric measurements: the temperature of partial homogenisation of the carbonic phases (in the presence of excess aqueous liquid), and the temperature of total homogenisation.